High grade prostatic intraepithelial neoplasia with squamous differentiation. Issue 4 (27th March 2006) - Melissari, M; Lopez Beltran, A; Mazzucchelli, R; Froio, E; Bostwick, D G; Montironi, R
Abstract : An unusual variant of prostatic intraepithelial neoplasia with prominent and extensive squamous differentiation is described. The lesion was identified in the transition zone of a 79 year old man with a three year history of increasing urinary obstructive symptoms and a clinical diagnosis of benign prostatic hyperplasia who underwent simple prostatectomy. Two years after surgery, prostatic biopsies showed atrophy and mild chronic inflammation, with no evidence of malignancy. This unusual intraepithelial lesion seems not to have been described before and may represent a new variant of high grade prostatic intraepithelial neoplasia (HGPIN) with squamous differentiation.